A realistic phantom for validating MRI‐based synthetic CT images of the human skull. Issue 9 (25th July 2017) - Soliman, Abraam S.; Burns, Levi; Owrangi, Amir; Lee, Young; Song, William Y.; Stanisz, Greg; Chugh, Brige P.
Abstract : Purpose: To introduce a new realistic human skull phantom for the validation of synthetic CT images of cortical bone from ultra‐short echo‐time (UTE) sequences. Methods: A human skull of an adult female was utilized as a realistic representation of skull cortical bone. The skull was stabilized in a special acrylic container and was filled with contrast agents that have T1 and T2 relaxation times similar to human brain. The phantom was MR scanned at 3T with UTE and T2 ‐weighted sequences, followed by CT. A clustering approach was developed to extract the cortical bone signal from MR images. T 2 ∗ maps of the skull were calculated. Synthetic CT images of the bone were compared to cortical bone signal extracted from CT images and confounding factors, such as registration errors, were analyzed. Results: Dice similarity coefficient (DSC) of UTE‐detected cortical bone was 0.84 and gradually decreased with decreasing number of spokes. DSC did not significantly depend on echo‐time. Registration errors were found to be significant confounding factors, with 25% decrease in DSC for consistent 2 mm error at each axis. Conclusion: This work introduced a new realistic human skull phantom, specifically for the evaluation and analysis of synthetic CT images of cortical bone.